Inhibition of Cdc42 and Rac1 activities in pheochromocytoma, the adrenal medulla tumor. (3rd April 2017) - Croisé, Pauline; Brunaud, Laurent; Tóth, Petra; Gasman, Stéphane; Ory, Stéphane
ABSTRACT: Altered Rho GTPase signaling has been linked to many types of cancer. As many small G proteins, Rho GTPases cycle between an active and inactive state thanks to specific regulators that catalyze exchange of GDP into GTP (Rho-GEF) or hydrolysis of GTP into GDP (Rho-GAP). Recent studies have shown that alteration takes place either at the level of Rho proteins themselves (expression levels, point mutations) or at the level of their regulators, mostly RhoGEFs and RhoGAPs. Most reports describe Rho GTPases gain of function that may participate to the tumorigenesis processes. In contrast, we have recently reported that decreased activities of Cdc42 and Rac1 as well as decreased expression of 2 Rho-GEFs, FARP1 and ARHGEF1, correlate with pheochromocytomas, a tumor developing in the medulla of the adrenal gland (Croisé et al., Endocrine Related Cancer, 2016). Here we highlight the major evidence and further study the correlation between Rho GTPases activities and expression levels of ARHGEF1 and FARP1. Finally we also discuss how the decrease of Cdc42 and Rac1 activities may help human pheochromocytomas to develop and comment the possible relationship between FARP1, ARHGEF1 and the 2 Rho GTPases Cdc42 and Rac1 in tumorigenesis.